2011
DOI: 10.1093/europace/eur028
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular pacing impairs endothelial function in man

Abstract: Right ventricular pacing is associated with worsened endothelial function and cardiac reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(38 reference statements)
0
4
0
1
Order By: Relevance
“…A high burden of RVA pacing has been associated with increased heart failure (HF) events in SND patients . Moreover, it has been postulated that RVA pacing has a detrimental impact on myocardial perfusion, oxygen demand, and left ventricular (LV) systolic function . Induction of interventricular or LV dyssynchrony by RVA pacing has been demonstrated acutely and at long‐term follow‐up and might be associated with long‐term deterioration of LV systolic function and HF .…”
Section: Introductionmentioning
confidence: 97%
“…A high burden of RVA pacing has been associated with increased heart failure (HF) events in SND patients . Moreover, it has been postulated that RVA pacing has a detrimental impact on myocardial perfusion, oxygen demand, and left ventricular (LV) systolic function . Induction of interventricular or LV dyssynchrony by RVA pacing has been demonstrated acutely and at long‐term follow‐up and might be associated with long‐term deterioration of LV systolic function and HF .…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Choy et al . reported that a higher percentage of right Vp compared with those with minimal Vp (90% vs. 15%) is associated with impaired endothelial function (measured using reactive hyperaemia in peripheral tonometry) as well as reduced cardiac reserve in patients with pacemakers. We postulate that the subsequent prolonged and persistent endothelial damage and dysfunction with Vp in long term may exacerbate the perpetuation of the atrial arrhythmia, as well as contributing to its prothrombotic state.…”
Section: Discussionmentioning
confidence: 99%
“…По литературным данным оценка ЭФ у пациентов с ЭКС осуществлялась косвенными методами, а именно определения количества метаболитов NO в крови и моче, использования метода трансторакальной импедансометрии у пациентов на фоне однокамерной желудочковой стимуляции [14,15]. При двухкамерной стимуляции ЭФ определялась с использованием метода кожной лазерной допплеровской флоуметрии в комбинации с ионофорезом с использованием ацетилхолина и нитропруссида натрия [4], индекса реактивной гиперемии артериол методом периферической артериальной тонометрии, определения амплитуды пульсовой волны при двухкамерной стимуляции с различной установкой атриовентрикулярной (АВ)-задержки [16]. Нет исследований, которые бы определяли ЭФ с применением эталонной пробы, предложенной Celermajer DJ [17].…”
Section: изменение эндотелиальной функции и внутрисердечной гемодинамunclassified